Strengthening Tuition Governance Towards Transparency and Accountability at Ummul Quro Al-Islami Modern Boarding School Bogor - Septiani, Dewi; Nugraha, Mulyawan Safwandy; Efendi, Efendi; Ramadhani, Ramadhani (STKIP Pesisir Selatan, 2024)
Qualified human resources are also a major contributor in motivating them to improve their performance. This helps the boarding school have no difficulty in encouraging all elements to work optimally, which in turn has a positive impact on the quality of education. Accountability and transparency play an important role in managing funds in educational institutions in order to ensure effective, efficient and fair management of educational funds. This research is a type of phenomenological research. The research subjects in this study were the person in charge of the pesantren, the pesantren finance director, the secretary of the finance director, the treasurer coordinator as the financing manager, and teachers/ustadz as participants in designing and implementing education financing in pesantren. Data collection techniques in this study used observation, interview and documentation methods. The results of this study indicate that Ummul Quro Al-Islami Bogor Islamic Boarding School has applied the principles of transparency and accountability in financial management by providing openness regarding income, details of use, and accountability to interested parties to find out.